FIRE INTENSITY EFFECTS ON BIODIVERSITY PATTERNS OF PLANTS IN MEDITERRANEAN WOODLANDS IN NORTHERN ALGERIA - Lillia Lembrouk, Ramdane Ramdini, Hamid Boudjelida (Chelonian Research Foundation, 2024)
Algeria, like several Mediterranean countries, was exposed to devastating wildfires. These fires are a key disturbance affecting plant biodiversity patterns and evolution, causing significant threats to lives, property and economic activity in the country. The Kabylia region, in particular, through the last few years, has undergone tragic consequences due to wildfires. In context, we assessed the recovery of floristic biodiversity and the soil-vegetation relationship, in order to evaluate the fire impact on this ecosystem. A qualitative inventory of plant species and a physico-chemical analyzes were carried out in the stations of Sidi Ali Bounab; considered as a reference site (A), since it was preserved from fires and the devastated Ikhelidjen site (B), with a big fire, in the Kabylia region (Northern Algeria). the survey was carriedout, during the spring (April- June) of the year 2022 and 2023, after 2021 big fires. The flora inventory, in Sidi Ali Bounab not burned site (A), revealed the presence of 55 species are belonging to 4 classes (Magnoliopsida, Equisetopsida, Liliopsida and Polypodiopsida) and to 50 genera, 31 botanical families, 25 orders, with the Asteraeae family dominance. At the same time, the flora survey in Ikhlidjen burned area revealed a total richness of 49 species belonging to 3 classes (Magnoliopsida, Liliopsida and Equisetopsida) spread over 43 genera, 20 families, and 19 orders. The flora regeneration was observed within the Asteraceae and Fabaceae families in a soil which presents a low alkaline and high organic matter content. The analyzes of the chemical properties, from both sites (A&B), showed that the quality of the soil favorized the installation and the diversification of the flora based on their loamy-sandy texture rich in organic, especially in the burned station and their pH as well as their electrical conductivity, which was confirmed by the ecological indices analyzes.